La gestion local de recursos forestales: la experienca Boliviana 94-98 - Kaimowitz, D. (1998)
This brief paper presents basic background information on decentralization in Bolivia and the role of municipal governments in forest management. Then it provides some possible lessons from the Bolivian experience for Central America. In concludes that decentralization opens new opportunities for local participation but does not gurantee that participation will occur or that benefits will be share more equitably. Informal power relations can be more important than formal changes in laws. Decentralisation's impact on the conservation of natural resources remains uncertain, with conflicting tendencies operating in both directions.